Balloon Inspired Conductive Hydrogel Strain Sensor for Reducing Radiation Damage in Peritumoral Organs During Brachytherapy. (23rd February 2022) - Guan, Lin; Liu, Hou; Ren, Xiaojun; Wang, Tiejun; Zhu, Weihang; Zhao, Yue; Feng, Yubin; Shen, Chun; Zvyagin, Andrei V.; Fang, Linan; Yang, Bai; Lin, Quan
Abstract: Conductive hydrogels have recently gained impressive attention in biological medicine and intelligent electronics. Despite the multifunctions demonstrated by existing conductive hydrogels, it is still a challenge to introduce a hydrogel to adjust the distance between the peritumoral organs and the tumor, reducing the radiation damage to the peritumoral organs. Here, a hydrophobic associating hydrogel with multiple desirable features is fabricated based on diverse supramolecular assembly. The introduction of MXene and hydrolyzed keratin (HK) imparts the hydrogel with excellent conductivity, ultra‐stretchability (>2000%), and good self‐adhesion. Moreover, the hydrogel is utilized as an intelligent sensor intended for monitoring various human movements and physiological signals, demonstrating a wide strain window, the rapid response time (130 ms), and outstanding strain sensitivity (GF = 10.22). Inspired by balloon inflation, the hydrogel is designed to separate the tumor from the peritumoral organs in brachytherapy. It plays a role in reducing the radiation dose and damage to the peritumoral organs. The authors also simulate the attenuation process of the radiation signal according to the change of the hydrogel size and develop a smartphone application (app) to monitor the safety range of the different radiation risks, manifesting its great potential in soft intelligent sensors. Abstract : A hydrogel‐based sensor with outstanding stretchability, excellent conductivity, and remodeling performance has been successfully designed. Inspired by balloon inflation, the hydrogel is designed to separate the tumor from the peritumoral organs in brachytherapy. The authors also simulate the attenuation process of radiation signals and monitor the safety range of different risks through an App.